Chimeric antigen receptor (CAR) T cell therapy in acute myeloid leukemia (AML) - Hofmann, Susanne; Schubert, Maria-Luisa; Wang, Lei; He, Bailin; Neuber, Brigitte; Dreger, Peter; Müller-Tidow, Carsten; Schmitt, Michael (Journal of Clinical Medicine, 2019)
Despite high response rates after initial chemotherapy in patients with acute myeloid leukemia (AML), relapses occur frequently, resulting in a five-year-survival by <30% of the patients. Hitherto, allogeneic hemotopoietic stem cell transplantation (allo-HSCT) is the best curative treatment option in intermediate and high risk AML. It is the proof-of-concept for T cell-based immunotherapies in AML based on the graft-versus-leukemia (GvL)-effect, but it also bears the risk of graft-versus-host disease. CD19-targeting therapies employing chimeric antigen receptor (CAR) T cells are a breakthrough in cancer therapy. A similar approach for myeloid malignancies is highly desirable. This article gives an overview on the state-of-the art of preclinical and clinical studies on suitable target antigens for CAR T cell therapy in AML patients.
Gesehen am 26.11.2024